RELATIVE FISHING POWER OP TRAWLERS OPERATED OFF COCHIN - Chakraborty, D; Banerji, S K (Indian Journal of Fisheries, 2011)
ALL vessels do not have same fishing power. The absolute fishing power of a vessel is measured in terms of the fishing mortality generated by it. But since the latter cannot be measured directly, a relative fishing power of a vessel has been defined as the ratio of the catch per unit fishing time of the vessel to that of another fishing vessel taken as standard when both are fishing on the same ground and the same density of fish. In this way, a fishing power can be allotted to each vessel. Once the relative fishing power of different vessels are known, it will be easy to Compute the total intensity of fishing effort, an accurate estimate of which is so essential in the study of stock assessments of fisheries